2018
DOI: 10.5014/ajot.2018.033415
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions for Weight Loss for People With Serious Mental Illness: A Systematic Review and Meta-Analysis

Abstract: Community-based interventions for people with SMI are effective for weight loss. Occupational therapists can be involved in the provision of weight loss interventions and in the development and study of intervention components that are most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Speyer et al and Vancampfort et al found that studies with an individual approach yield higher effects on weight outcomes [ 12 , 13 ]. In contrast, other reviews state that group interventions would be more effective and highlight the importance of peer support for motivation [ 73 , 76 , 77 ]. Our own analysis showed a tendency of larger benefits of group settings on QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Speyer et al and Vancampfort et al found that studies with an individual approach yield higher effects on weight outcomes [ 12 , 13 ]. In contrast, other reviews state that group interventions would be more effective and highlight the importance of peer support for motivation [ 73 , 76 , 77 ]. Our own analysis showed a tendency of larger benefits of group settings on QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of screening programmes assessing overweight and obesity might be useful to identify people at higher risk, and referral to lifestyle interventions and collaborative care as suggested by the WHO guidelines for management of physical conditions in adults with SMI ( 8 ). Despite the multiple barriers faced by this population such as stigma, illness symptoms and low motivation, the few pharmacological and lifestyle interventions available to prevent and treat obesity in this population have proven to be effective to maintain and reduce body weight ( 39 42 ). In addition, they have shown benefits in other parameters such as fasting blood glucose, hypertension and dyslipidemia ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, weight loss interventions, including specific programmes designed for patients with psychosis, have shown limited clinical benefits for patients with psychosis Brown et al, 2018;Naslund et al, 2016;Speyer et al, 2019). Greater effectiveness is apparent for interventions self-worth and changed appearance amplified a sense of vulnerability.…”
Section: Backgrou N Dmentioning
confidence: 99%